2007
DOI: 10.1523/jneurosci.0055-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Docosahexaenoic Acid and Docosapentaenoic Acid Ameliorate Amyloid-β and Tau Pathology via a Mechanism Involving Presenilin 1 Levels

Abstract: The underlying cause of sporadic Alzheimer disease (AD) is unknown, but a number of environmental and genetic factors are likely to be involved. One environmental factor that is increasingly being recognized as contributing to brain aging is diet, which has evolved markedly over modern history. Here we show that dietary supplementation with docosahexaenoic acid (DHA), an n-3 polyunsaturated fatty acid, in the 3xTg-AD mouse model of AD reduced the intraneuronal accumulation of both amyloid-␤ (A␤) and tau. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
279
4
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(307 citation statements)
references
References 57 publications
18
279
4
6
Order By: Relevance
“…Our own and previous work from other groups indicate that dietary DHA significantly improves cognitive deficits, protects from synaptic protein loss, and lowers insoluble A␤ in transgenic AD mouse models (Calon et al, 2004;Lim et al, 2005;Oksman et al, 2006;Ma et al, 2007). Our current data are consistent with a report that algal DHA reduced A␤ accumulation, suggesting this effect may have reduced JNK activation and ptau in 3xTg-AD mice (Green et al, 2007), but the effects we observed need not be secondary to A␤ reduction because we show that DHA reduces the JNK, IRS-1, and tau phosphorylation response to exogenous A␤ oligomers. Both protective activities are likely, but we did not find robust A␤ labeling at 9 months in the line of 3xTg-AD mice on the diets used.…”
Section: Discussionsupporting
confidence: 92%
“…Our own and previous work from other groups indicate that dietary DHA significantly improves cognitive deficits, protects from synaptic protein loss, and lowers insoluble A␤ in transgenic AD mouse models (Calon et al, 2004;Lim et al, 2005;Oksman et al, 2006;Ma et al, 2007). Our current data are consistent with a report that algal DHA reduced A␤ accumulation, suggesting this effect may have reduced JNK activation and ptau in 3xTg-AD mice (Green et al, 2007), but the effects we observed need not be secondary to A␤ reduction because we show that DHA reduces the JNK, IRS-1, and tau phosphorylation response to exogenous A␤ oligomers. Both protective activities are likely, but we did not find robust A␤ labeling at 9 months in the line of 3xTg-AD mice on the diets used.…”
Section: Discussionsupporting
confidence: 92%
“…This form of LTP depends upon mature granule neurons synaptic activity (Saxe et al, 2006). The modulation of PICRO-LTP might be due to the blockage of hippocampal microglia activation as previously reported in different animal models (Calon et al, 2005) (Green et al, 2007) (Fig. 4).…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, DHA reduced amyloid ␤ 42 (A␤42) in AD mice (Lim et al, 2005;Oksman et al, 2006;Green et al, 2007;Hooijmans et al, 2007) and production by cultured human neurons (Lukiw et al, 2005). The mechanism involved in the DHAinduced reductions in A␤42 may be due to multiple effects, such as: changes in lipid raft structure (Stillwell et al, 2005), alterations in APP processing (Ehehalt et al, 2003), induction of antiamyloidogenic chaperones for APP , and A␤ transthyretin (Schwarzman et al, 1994;Puskás et al, 2003).…”
Section: Walnut and Fish Polyunsaturated Fatty Acidsmentioning
confidence: 99%